Assessing Service Quality in the Ghanaian Private Healthcare Sector: The Case of Comboni Hospital. (International Journal of Scientific Research and Management (IJSRM), 2020)
The healthcare industry has become a paramount concern for most people in Ghana and the quality of services rendered to the patients in the private hospitals cannot be overemphasized. Patients need quality of services most and are willing to seek better services. The government has been the main provider of health care services in Ghana but recently, some Non-Governmental Organization’s (NGO’s), private individuals and stakeholders also provide health care services which has surged the competitiveness in creating more healthcare facilities in Ghana. This study seeks to explore patients’ choice of selecting quality healthcare services and the factors that affect patient satisfaction in private hospitals using the Comboni Hospital in Sogakope, Ghana. The study therefore used the quantitative research method to collect the data and SPSS version 22 was used to analyze the data on high-quality healthcare. Also, the SERVQUAL model was used as the measurement scale. Multiple regression analysis was used to reveal the effect of the independent variables (reliability, responsiveness, empathy, assurance, and tangibility) on the dependent variable (patient satisfaction). A detailed description in the analysis and the data processing identified the main factors affecting the general perceptions and patient preferences about their healthcare in the private hospital. The study revealed that there exist a positive result and perception for quality healthcare services without a negative expectation of the patient healthcare being compromised. In this case, the study recommends that both the government and the private agencies should consider the important aspects of hospital’s healthcare management and also the policy and decision makers should have an efficient and effective standard that impact the quality of healthcare assessment in Ghana.